2014
DOI: 10.2214/ajr.13.12256
|View full text |Cite
|
Sign up to set email alerts
|

FDG PET/CT in the Management of Colorectal and Anal Cancers

Abstract: FDG PET/CT is a valuable imaging modality that impacts the clinical management of patients with CRC and those with anal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(31 citation statements)
references
References 84 publications
1
26
0
1
Order By: Relevance
“…Treatment with chemotherapy causes a reduction of SUV within the tumor or metastases often before morphological changes become visible. This can be used for treatment or response monitoring [78]. Furthermore, several reports indicate that SUVmax or reduction of SUV after treatment can be used as prognostic factors for tumor recurrence or overall survival [78,79].…”
Section: Ultrasonographymentioning
confidence: 99%
See 2 more Smart Citations
“…Treatment with chemotherapy causes a reduction of SUV within the tumor or metastases often before morphological changes become visible. This can be used for treatment or response monitoring [78]. Furthermore, several reports indicate that SUVmax or reduction of SUV after treatment can be used as prognostic factors for tumor recurrence or overall survival [78,79].…”
Section: Ultrasonographymentioning
confidence: 99%
“…Furthermore, several reports indicate that SUVmax or reduction of SUV after treatment can be used as prognostic factors for tumor recurrence or overall survival [78,79]. PET/CT has also the potential to improve radiation therapy by optimization of the planning target volumes and subsequently radiation dose [78].…”
Section: Ultrasonographymentioning
confidence: 99%
See 1 more Smart Citation
“…PET/CT is currently recommended by the American College of Radiology for staging of large rectal cancers because results of studies have shown that use of this modality may accurately change the staging or influence treatment planning for this subset of patients (34,39). Results of several metaanalyses have shown PET/CT to be superior to CT for use in detection of hepatic metastases (40,41). One scenario in particular that may be amenable to PET/CT evaluation is exclusion of occult metastases in patients being considered for liver metastectomy with curative intent (26).…”
Section: Initial Assessment Rectal Cancermentioning
confidence: 99%
“…In a small study of 34 patients with T3-T4, N0-N1, and M0-M1 disease, Whaley et al (44) found that PET/CT altered staging in 18% of patients and improved interobserver concordance in contouring boost treatment volumes compared with CT alone. This may be due to the superior ability of PET/ CT to delineate tumor volume, which serves to minimize treatment margins and exclude nondiseased tissue (40).…”
Section: Initial Assessment Rectal Cancermentioning
confidence: 99%